Sistem Pendukung Keputusan Pemilihan Aplikasi Chat Terbaik Dalam Mendukung Pembelajaran Daring di Masa Pandemi Covid Menggunakan Metode Multi Attribute Utility Theory - Mesran Mesran; Amanudin Harahap; Fifto Nugroho (Universitas Budi Darma, 2023)
The Chating application is a virtual communication service either through messages, voice calls, or video calls that can assist in conducting online lectures during a pandemic. There are many types of applications that can be used to communicate during online lectures. Such as the Telegram application, Whatsapp application, Discord, KaKaoTalk, Line or WeChat and other social media applications that can be used to communicate personally or in groups. However, these applications have their own advantages and disadvantages that can affect the comfort and optimization of learning. Therefore, to determine the best Chating application, each alternative must have its own criteria as a requirement for the optimization of the application. As in this study, the authors added some data as criteria, namely Group Support, Member Capacity, Security, Account Privacy and Services provided by the application. Which, each criterion has a predetermined weight and is carried out with a settlement process using the Multi Attribute Utility Theory (MAUT) method for the ranking process. From calculations using the Multi Attribute Utility Theory (MAUT) method, it will produce sequential alternatives from the highest to the lowest. The alternative value which is Qi or the highest ranking will be used as an alternative recommendation for chat applications that will be used as a tool to support online learning during the Covid pandemic.